ANALISIS PENGARUH MARKETING MIX (7P) TERHADAP MINAT BELI ULANG PADA TOKO BUKU GRAMEDIA PANGKALPINANG - Pradita, Kin Kin; Manullang, Rizal Ruben; Mulyani, Hendarti Tri Setyo (Jurnal Progresif Manajemen Bisnis, 2023)
This study aims to analyze the influence of the 7Ps in the marketing mix, namely product, price, place, promotion, people, process, and physical evidence on repurchase intention at the Gramedia Pangkalpinang bookstore. Respondents in this study were customers of the Gramedia Pangkalpinang bookstore. Data analysis was performed using multiple linear regression methods. The results of the study show that all 7Ps in the marketing mix have a significant influence on repurchase intention at the Gramedia Pangkalpinang bookstore. Product has the greatest influence on repurchase intention. followed by price, place, and promotion. People, process, and physical evidence have a smaller but still significant influence on repurchase intention. The consequence of the results of this study is that the Gramedia Pangkalpinang bookstore must pay attention to all 7P's in the marketing mix in order to increase customer repurchase interest. The results of the study show that Marketing Mix (7p) has an effect on Repurchase Interest with tcount values -0.879, 2.934, 0.750, 3.834, -1.428, 0.850, 2.718 with ttable values 1.661585 and Fcount values 8.987 Ftable 2.11. Thus, it can be stated that Product, Price, Location, People, Promotion, Process, Physical Environment are proven to influence Repurchase Interest at Gramedia Pangkalpinang Bookstore.